Museums in the new mediascape transmedia, participation, ethics - Kidd, Jenny (Farnham, Surrey, England Ashgate, 2014)
"The museum today faces complex questions of definition, representation, ethics, aspiration and economic survival. Alongside this we see burgeoning use of an array of new media including increasingly dynamic web portals and content, digital archives, social networks, blogs and online games. At the heart of this are changes to the idea of 'visitor' and 'audience' and their participation and representation in the new cultural sphere. This insightful book unpacks a number of contradictions that help to frame and articulate digital media work in the museum and questions what constitutes authentic participation. Based on original empirical research and a range of case studies the author explores questions about the museum as media from a number of different disciplines and shows that across museums and the study of them, the cultural logic is changing"--Provided by publisher.
The transmedia museum -- Museum communications in social networks -- User created content -- Democratising narratives: or, The accumulation of the digital memory archive -- "Interactives" in the social museum -- Museum online games as empathy encounters -- Mashup the museum.
Includes bibliographical references (pages 135-160) and index.
Keywords: Museums -- Social aspects; Museums -- Technological innovations; Museums -- Moral and ethical aspects; Interactive multimedia; Narration (Rhetoric) -- Social aspects; Digital media; Social media; Electronic games; Museum visitors; Participation